Stochastic Frontier Production Function and Efficiency Status of Poultry Layer Farms in Malaysia - Elpawati,; Gabdo, Bashir Hamman; Ismail, Mohd Mansor; Abdurofi , Ilmas (International Journal of Poultry Science, 2018)
Background and Objective: The high cost of production, in particular feed costs in poultry production, is alarming. This study was conducted to identify patterns of production and sources of waste in resource utilization. Materials and Methods: Stochastic frontier production function (SFPF) model was used to measure the output elasticities and investigate the inefficiency effect in Malaysia’s poultry layer farms. Results: Our findings reveal output elasticities of 1.461 (p